"When in Rio":: questões midiáticas de foliões cariocas - Barata, Luiza Cunha; Gonzaga, Francisco Lemos dos Santos Alves (Revista do Colóquio, 2020)
The relationship between the street carnival in Rio de Janeiro and the government has undergone significant changes in recent years. If there is more rigor to the procession, there is also more creativity of revelers to circumvent official decrees and put the “block on the street”. This article presents an analysis of alternative media territories that participants find to publicize and integrate the mega event. For this, experiences of the so-called unofficial blocks and messages from the Telegram group “When in Rio” will be analyzed.